2014
DOI: 10.1159/000360102
|View full text |Cite
|
Sign up to set email alerts
|

The Thrombotic Events in Polycythemia Vera Patients May Be Related to Increased Oxidative Stress

Abstract: Objective: This study was designed to compare the oxidative stress parameters of patients with polycythemia vera (PV) to those of healthy volunteers and to investigate the probable relationship between vascular events and parameters of oxidative status such as total oxidative status (TOS), total antioxidant status, oxidative stress index (OSI) and malondialdehyde (MDA) in PV patients. Material and Methods: Thirty-five PV patients (20 males and 15 females) and 20 healthy volunteers (11 males and 9 females) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…In view of the fact that, JAK2 activates nonreceptor tyrosine kinase (NRTK) cascade 20 and in our recent study increased ROS (reactive oxygen species; oxidative stress) levels were detected in the PV patients having JAK2 mutation, 16 we further hypothesized that JAK2 activates tyrosine kinase by increasing ROS production. Hence, this might be one of the possible pathways of lentiginosis (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In view of the fact that, JAK2 activates nonreceptor tyrosine kinase (NRTK) cascade 20 and in our recent study increased ROS (reactive oxygen species; oxidative stress) levels were detected in the PV patients having JAK2 mutation, 16 we further hypothesized that JAK2 activates tyrosine kinase by increasing ROS production. Hence, this might be one of the possible pathways of lentiginosis (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…PV is seen in older ages particularly under the effect of acquired somatic mutation of JAK2 (V617F) 14,15 that the latter is a diagnostic parameter of the disease. 16 JAK2 is a member of the Janus kinase family of nonreceptor protein tyrosine kinases and has an important role in the cellular development and homeostasis. 17 Though, overactivity of the JAK2, chiefly under the effect of JAK2 (V617F) mutation, is well-known in myeloproliferative neoplasms, 16,18,19 its effect in melanocytic disorders has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Numerous studies have shown a high oxidative status in patients with chronic myeloproliferative neoplasms, a situation that correlates with a higher thrombotic risk. 32,36,37 Although associations of increases in oxidative stress with MPN have been identified, association with changes in membrane fluidity and thrombocyte function remains to be investigated. 32,38 The presence of circulating micro particles plays an important role in the occurrence of thrombosis in patients with chronic myeloproliferative disorders.…”
Section: 32mentioning
confidence: 99%
“…Oxidative stress is associated with disruption of the prooxidant and antioxidant balance [8]. It results from either overproduction of free oxygen radicals or insufficiency of antioxidant mechanisms [6].…”
Section: Introductionmentioning
confidence: 99%
“…In response to increased oxidative stress, living organisms develop an antioxidant defense against the harmful effects of free oxygen radicals. Individual measurement of all the different antioxidants is difficult due to the workload involved in the laboratory, the high costs incurred, the complex techniques required and the interaction of serum antioxidants [8].…”
Section: Introductionmentioning
confidence: 99%